Learning design and transdisciplinary pedagogical templates (TPTs) - Dobozy, Eva; Dalziel, J.; Dalziel, B. (Libri Publishing, 2012)
In a move to professionalise the future workforce, paradigmatic changes are required to the way in which university education is conducted. The greater adoption of Learning Design principles and the successful dissemination of knowledge-centric transdisciplinary pedagogical templates (TPTs) for use in various contexts may provide a possible way forward. This chapter explores the implementation of Learning Design principles through the development of knowledge-centric TPTs and gauges initial practitioner reactions. The benefits of knowledge-centric TPTs for the renewal of university education are discussed and some obstacles in pilot implementations of scenario-based designs in medical and teacher education are explored.